Upaya Meningkatkan Kecerdasan Visual Spasial Anak Usia Dini melalui Bermain Tebak Gambar: Efforts to Improve Early Childhood Visual Spatial Intelligence through Playing Guess the Picture - Barus, Nadilla; Chintya, Risma; Sukmana, Khalida Ziah; Sit, Masganti (Absorbent Mind, 2024)
Visual-spatial intelligence is something that children possess. With this intelligence, young children can visualize various activities through activities that can sharpen their minds. This study aims to determine whether playing with guessing pictures can improve the development of visual-spatial intelligence in early childhood at Tk. Citra Mandiri Batang Kuis by knowing how playing guessing pictures can improve the development of visual-spatial intelligence in early childhood group B at Tk. Citra Mandiri Batang Kuis. Based on teacher research in a learning process lacking the method of playing guessing pictures in improving the development of children's spatial-visual intelligence, a class action research method (PTK) was used in the research. Data sources, namely observation and interviews, were used. From the results of the data obtained, it is concluded that in an effort to improve the visual-spatial intelligence of early childhood through playing guess the picture in the pretest, an average of 30% of the criteria is starting to develop (MB). The protest reached an average of 80%, with the criteria developing as expected (BSH). From the results of research on visual-spatial intelligence of early childhood through playing, the picture has increased to reach the criteria for visual indicators of child development.